Investasi syariah dalam meningkatkan profitabilitas PT. Asuransi Takaful Keluarga di tengah tantangan ekonomi global - Budiman, Ardiyan; Humaemah, Ratu; Surahman, Surahman; Jambunanda, Ahmad Jamaludin (AL-Muqayyad, 2025)
This research examines how the implementation of sustainable Islamic investment can encourage profit growth at PT. Asuransi Takaful Keluarga. This study aims to analyze the effect of the implementation of sustainable sharia investment on the profit growth of PT. Asuransi Takaful Keluarga in the midst of global economic challenges. Through a qualitative approach, this study found that the implementation of sustainable Islamic investment contributed significantly to the increase in company profits. This is due to several factors, including increased investor confidence and reduced operational risk. This research shows that sustainable Islamic investment is not only limited to fulfilling social and environmental aspects, but can also be an effective business strategy to improve the company's financial performance.